A video processing pipeline for intraoperative analysis of cerebral blood flow. Issue 4 (3rd July 2020) - Klemm, Sören; Rexeisen, Robin; Stummer, Walter; Jiang, Xiaoyi; Holling, Markus
ABSTRACT: In this paper, we propose a pipeline for non-invasive, high-resolution analysis of cerebral blood flow. We use a 3-CMOS HD-Videocamera to record video samples that are processed by a stabilization and colour amplification pipeline to visualize changes caused by the blood pressure cycle. To our knowledge, this is the first description of a non-invasive, only software-based algorithm which comprises information about brain perfusion.